The cooperative sector in San Luis, Argentina. A recognition of the expressions of the capital city - Hidalgo, Ana Laura (2023)
The purpose of this article is to present the cooperative sector of the city of San Luis recognized until May 2022. The work systematizes a series of specific antecedents of other relevant contributions that, within the framework of the Social and Solidarity Economy, carried out similar investigations. in other territories of our country and in Latin America. Secondary information sources were consulted, which were processed in a characterization that aims to provide inputs for subsequent approaches that contribute to making the sector visible and strengthening. In the development, it is shown that the formal labor market is strongly concentrated in private actors, or in public organizations; This reveals that few workers are registered in cooperative activities as part of the SSE sector in San Luis.